Outcomes after antibiotic megaspacer implantation in patients with severe chronic periprosthetic infections. Issue 2 (25th November 2020) - Amin, Sheena J.; Patel, Raj M.; Gutowski, Christina J.; Kim, Tae Won B.
Abstract: Periprosthetic joint infection (PJI) is a rare postoperative complication that is treated with antibiotic spacers. Some patients develop severe, treatment‐resistant, chronic PJI despite multiple attempts at salvaging the joint. Permanent resection of the joint or amputation may be the only definitive treatment. The purpose of this study is to describe the outcomes, infection resolution rate, and complications of two‐stage revision, utilizing extensive resection of the affected bone and application of antibiotic megaspacers as a modality for limb‐salvage. A review of 12 patients, initially referred for amputation due to chronically failed PJI, was conducted. All patients underwent extensive resection of the bone and surgical implantation of a custom‐made antibiotic megaspacer between December 2016 and June 2019. Thirteen megaspacers were placed in 13 infected joints in 12 patients with a history of chronic PJI. Six patients (50%) had a diagnosis of osteomyelitis. Eradication of the infection leading to limb‐salvage was successful in nine patients. Visual Analog Scale pain scores improved by 3.5, or 50%, after two‐stage revision with megaprosthesis reimplantation ( p  = .008), and six patients (54.5%) had improvement in ambulation. Complication rates, not including reinfection or recurrence, following megaspacer and megaprosthesis reimplantation were 58.3% and 27.3%, respectively. One patient underwent amputation due to a life‐threatening infection while two other patients underwent amputation due to debilitating complications following limb‐salvage surgery. Statement of Clinical Significance : In patients whose PJI becomes treatment‐resistant after multiple failed attempts at traditional two‐stage exchange, performing extensive boney resection with placement of an antibiotic‐laden megaspacer can be an effective method of achieving limb‐salvage.